Contribuição na delimitação de espécies do gênero neotropical Dimorphandra Schott (Leguminosae: Caesalpinoideae) - Silva, Guilherme Sousa da (Instituto Nacional Pesquisas da Amazônia - INPA, 2023)
Dimorphandra Schott is the genus with the largest number of taxa described (26 species) circumscribed in the Leguminosae Family, subfamily Cesalpinoideae, Caesalpinieae tribe, Dimorphandra group, distributed exclusively in the Neotropics, adding three subgenera: Dimorphandra, Pocillum and Phaneropsia, being differentiated by leaves, shape of the inflorescence and fruit. The genus is polyphyletic, having three distinct lines that correspond to the three sections of the genus, but due to the low sampling of species and individuals with sequenced markers, the phylogeny is still under development. The taxonomic knowledge of the group is summarized so far, but with several gaps, both in the description of the species by the lack of more complete collections and by the problems of morphological overlap of some taxa that hinder or leave uncertainties in their delimitation. Because each taxonomic approach accesses a different type of information, several tools are necessary in the taxonomic delimitation and a tool currently used in species discrimination is near infrared spectroscopy (NIRS), demonstrating significant results. In this way the research aims to contribute to the delimitation of the taxa that make up the neotropical genus Dimorphandra (Leguminosae-Caesalpinioideae), using morphological data to produce a taxonomic treatment and spectral data as a tool to discriminate species. The production of the treatments was based entirely on taxonomic analyzes of herbarium specimens from national and international herbariums and when possible on natural material and field observations from August 2017 to August 2018. Results are provided as descriptions morphological of the characteristics of species and subgenera, identification keys, distribution maps, flowering and fruiting data, and comments on affinities and important diagnostic characters in the determination of taxa. With the taxonomic treatments the main differences and affinities between the subgenera of Dimorphandra are clarified, making evident the presence of diagnostic characters for better distinction and few characters with morphological overlap, corroborating with the phylogenetic hypothesis that the lineages are quite distinct. Regarding the problems of species delimitation, several characters are presented for a better determination of the taxa, especially in the cases of D. gardneriana and D. mollis, the subspecies of D. macrostachya and D. cuprea and the specific problems of D. campinarum, D. mediocres, D. multiflora, D. conjugata that presented structures without description or doubts in their recognition. Twenty-two new records are recognized, 15 for Brazilian states and seven for South American countries, with the recognition of 21 species for Brazil. From the spectral analyzes, spectra of leaflets of 315 individuals were collected with standardization of six readings per individual, distributed in 20 species of Dimorphandra. Principal Component Analysis (PCAs) were performed to visualize the spectral behavior and to generate discriminant functions in order to evaluate the potential of the data to correctly distinguish the species. The PCAs were efficient in understanding the spectral behavior, mainly in the separation and grouping of some taxa, and the prediction values ranged from 92-95%, using the 70-30 validation test in the discriminant analysis (LDA). It is inferred that the use of near-infrared spectroscopy (NIRS) has proved to be an important tool for discriminating species of the genus Dimorphandra, contributing to the determination of taxa.
Keywords: Taxonomia de Legumuninosas; Diversidade florística amazônica